Relevance and feasibility of women's involvement in promoting sustainable food production and security in Southern Africa - Assan, Never (Sustainability in Debate, 2014)
Harnessing women’s potential for food production and security has been a challenge in Southern Africa. The face of food production in Southern Africa is often female, but more often than not, their roles are generally undervalued and constrained by gender inequalities and limitations on their access to resources, services, and market opportunities. This chapter explores how women involvement in food production can have a positive impact on food security in Southern Africa. The gender aspect of food security assume significance, as it is widely recognized that women are the custodian of food production in many communities in Southern Africa. There is a tendency of men and women participating unevenly in food production, have unequal access to productive resources and exhibit different levels of engagement in rural, urban and home-based food production. Despite this anomaly, there is still a common understanding that food production needs to be increased in order to cope with the increased human population and achieving food security in the region. With this in mind, food production and security have emerged as key development targets in Southern Africa. This has propelled the urgent need for promoting food production, reducing food insecurity and poverty reduction in its totality. One of the factors contributing to perpetual low food production and insecurity has been gender discrimination and/or lack of participation of women in agricultural programs and projects. In this chapter there is an attempt to describe the impact of gender-based discrimination on food production and its implication on food security. The indispensable role and challenges faced by women in food production are highlighted. The need to invest in education and training of women to support food production systems in order to accrue maximum benefit is acknowledged. In this regard, it is imperative that planning and implementation of any food production programs focusing on improving food security should be based on gender sensitive policies. Policies which give women due recognition as far as food production decision making processes are concerned are sought. The chapter concludes with the understanding that involvement of women in food production becomes a key component of addressing food insecurity in Southern Africa. The vulnerability of people in Southern Africa to food insecurity depends both on measures that can be implemented in a given context and the capacity of families, and women in particular, to respond to food shortages. It is important, therefore that food security remains high on the regional development agenda. The region should prioritize appropriate interventions which help women fully participate in food production and develop sustainable livelihoods.